2019
DOI: 10.1039/c9fo01500k
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of cranberry polyphenol and volatile extracts on nitric oxide production in LPS activated RAW 264.7 macrophages

Abstract: Cranberry volatiles have received little attention for health-promoting properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…Cranberry is well known for its inhibitory action on NO production. Moore et al suggested that cranberry polyphenol and volatile extracts induced a 46-fold decrease in NO production in LPS-activated RAW 264.7 macrophages [38]. In the present study, SHE caused 38% inhibition of NO production induced by LPS in RAW 264.7 cells.…”
Section: Discussionsupporting
confidence: 61%
“…Cranberry is well known for its inhibitory action on NO production. Moore et al suggested that cranberry polyphenol and volatile extracts induced a 46-fold decrease in NO production in LPS-activated RAW 264.7 macrophages [38]. In the present study, SHE caused 38% inhibition of NO production induced by LPS in RAW 264.7 cells.…”
Section: Discussionsupporting
confidence: 61%
“…Strawberry extract (100 μg/mL) also a showed significant decrease in LPS-stimulated NO production, compared to the control without LPS ( p < 0.05) [ 92 ]. In a recent study, Moore et al [ 28 ] compared the NO-inhibitory effect of cranberry polyphenols and volatiles. Both cranberry polyphenol (317.8 and 635.7 μg/g) and volatile (1.8 μg/g) extracts significantly suppressed LPS-induced NO production ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Berry volatile extract (200 mL) was collected in an ice bath incubated flask and stored at −20 °C until use. Solid phase micro-extraction (SPME) of volatiles was performed using a 85 μm, CAR/PDMS, Stableflex, 24 Ga, Manual Supelco (Bellefonte, PA, USA) SPME fiber as previously described [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Little research has been conducted on the anti-inflammatory effect of blackberry volatiles, but studies have demonstrated the anti-inflammatory capacities of essential oils that contain common blackberry volatiles (Hirota et al, 2010;Huo et al, 2013;Plastina et al, 2018). Moreover, in a recent study by Moore et al (2019), phenolic and volatile extracts isolated from cranberries, as well as each of the four most abundant volatiles in cranberries, αterpeniol, linalool oxide, eucalyptol, and linalool were tested at concentrations found in fresh cranberries for their anti-inflammatory capacities, before or after inflammation of RAW264.7 murine macrophage cells. When applied as a treatment after induction of inflammation in the cells, not only did the cranberry volatiles decrease nitric oxide (NO) production by the inflamed cells, but their effect was comparable to that of cranberry phenolics, even though they were 353 times less concentrated.…”
mentioning
confidence: 99%